TREATMENT SYSTEM, MEDICAL IMAGE PROCESSING DEVICE, AND TREATMENT PROGRAM - SAKATA KOSHIN; MORI SHINICHIRO; TAGUCHI YASUNORI; YAZAWA TAKASHI; HIRAI RYUSUKE (2017)
PROBLEM TO BE SOLVED: To provide a treatment system capable of irradiating a treatment beam more accurately, a medical image processing device, and a treatment program.SOLUTION: A treatment system includes an irradiation part, an acquisition part, an affected part detection part, a reference region detection part, and an irradiation control part. The irradiation part irradiates a treatment beam onto a subject. The acquisition part acquires a transparent image of the subject. The affected part detection part detects an affected part of the subject based on the transparent image acquired by the acquisition part. The reference region detection part detects a reference region of the subject based on the transparent image acquired by the acquisition part. The irradiation control part controls the irradiation part so as to irradiate the treatment beam onto the subject if the relationships between the affected part detected by the affected part detection part and the reference region detected by the reference region detection part satisfy a predetermined condition.SELECTED DRAWING: Figure 2 【課題】より正確に治療ビームを照射することができる治療システム、医用画像処理装置、および治療プログラムを提供することである。【解決手段】実施形態の治療システムは、照射部と、取得部と、患部検出部と、参照部位検出部と、照射制御部とを持つ。前記照射部は、被検体に対して治療ビームを照射する。前記取得部は、前記被検体の透視画像を取得する。前記患部検出部は、前記取得部により取得された前記透視画像に基づき、前記被検体の患部を検出する。前記参照部位検出部は、前記取得部により取得された前記透視画像に基づき、前記被検体の参照部位を検出する。前記照射制御部は、前記患部検出部によって検出された前記患部と、前記参照部位検出部によって検出された前記参照部位との関係が所定の条件を満たす場合、前記治療ビームを前記被検体に照射するよう前記照射部を制御する。【選択図】図２